Franquias Virtuais, uma Nova Estratégia para os Varejistas no E-Commerce - Paula Narita Pereira Ebert (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2018)
The main goal of this study is to analyze the development of a new distribution channel virtual franchise, based on the perceptions of the virtual franchise consultants and their respective consumers. The study is based on a qualitative, exploratory and descriptive research, it is a case study and used netnographic research and participant observation applied to franchisees and virtual consumers of the Natura Network. The virtual franchise stands out due to the low cost of operating investment, for the easy access and a business system already developed and evaluated, by legal using of a conceptualized yet in the market and in function of the tranquility in the infrastructure provided by the franchisor. The essential task of the digital franchisee is the sale by relationship. The results show social, economic and academic contributions, once they contribute to the literature by the contemporaneity of the subject.